Multiple constraints on urban bird communication: both abiotic and biotic noise shape songs in cities. (13th July 2021) - To, Ann W Y; Dingle, Caroline; Collins, Sarah A
Abstract: Ambient noise can cause birds to adjust their songs to avoid masking. Most studies investigate responses to a single noise source (e.g., low-frequency traffic noise, or high-frequency insect noise). Here, we investigated the effects of both anthropogenic and insect noise on vocalizations of four common bird species in Hong Kong. Common Tailorbirds ( Orthotomus sutorius ) and Eurasian Tree Sparrows ( Passer montanus ) both sang at a higher frequency in urban areas compared to peri-urban areas. Red-whiskered Bulbuls ( Pycnonotus jocosus ) in urban areas shifted the only first note of their song upwards. Swinhoe's White-eye ( Zosterops simplex ) vocalization changes were correlated with noise level, but did not differ between the peri-urban and urban populations. Insect noise caused the Eurasian Tree Sparrow to reduce both maximum, peak frequency, and overall bandwidth of vocalizations. Insect noise also led to a reduction in maximum frequency in Red-whiskered bulbuls. The presence of both urban noise and insect noise affected the sound of the Common Tailorbirds and Eurasian Tree Sparrows; in urban areas, they no longer increased their minimum song frequency when insect sounds were also present. These results highlight the complexity of the soundscape in urban areas. The presence of both high- and low-frequency ambient noise may make it difficult for urban birds to avoid signal masking while still maintaining their fitness in noisy cities. Abstract : Studies have shown that birds increase their vocalization pitch under low-frequency urban noise and sing at a lower pitch when exposed to high-frequency insect sounds, but what if they occur simultaneously? Using field recordings, we found that some urban birds no longer adjusted their song in response to urban noise when insect noise is also present. This shows that anthropogenic noise is not the only driver of changes in urban bird songs.